Multifunctional magnetically responsive biocomposites based on genetically engineered silk-elastin-like protein. (15th November 2018) - Fernandes, M.M.; Correia, D.M.; da Costa, A.; Ribeiro, S.; Casal, M.; Lanceros-Méndez, S.; Machado, R.
Abstract: Magnetic nanocomposite films, comprised of a genetically engineered silk-elastin-like protein (SELP) and CoFe2 O4 nanoparticles (CFO NPs) with concentrations varying between 5 and 20 wt%, were produced by solvent casting. The obtained materials were analysed regarding their morphology, physical-chemical, thermal, mechanical and magnetic properties. It was found that the magnetic NPs are homogenously distributed among the film and do not induce any significant alterations in their physical-chemical properties. Regarding the thermal properties, the onset degradation temperature of the SELP-59-A films was also not significantly altered by the inclusion of the NPs. Further, strongly bound water is present in the material, which decreases with increasing NPs concentration. Likewise, the mechanical properties of the films were affected by the presence of NPs. Finally, it was demonstrated that the magnetization saturation increases with increasing CFO NPs content, showing the magnetic responsivity of the materials and opening new perspectives in the development of a new generation of multifunctional biocomposites suitable for a wide range of applications, from sensors to tissue engineering.